Teoria social e dialógica do sujeito - José Antônio Damásio Abib (Psicologia, 2005)
This essay presents the social and dialogical theory of the self, elaborated by George Herbert Mead, the North American pragmatist philosopher and social psychologist. According to his theory, communicative and participative action - the social action that involves the sharing of meanings - is the social basis of language formation, of the mind and of the self. Mead conceives the subject as a relation involving the I and the me. The me is the social subject, reproducing the social order. The I is, not only the biological or impulsive subject, but also the observer, cognitive, critical and agent of social change. Cognition results from this relation and develops as the process of control of impulse and of reflexive and moral deliberation. By way of conclusion, it is shown in what sense Mead's social-cognitive behaviorism, guided by philosophical pragmatism, may contribute to the cognitive-behavioral approach.